2013
DOI: 10.1002/polb.23276
|View full text |Cite
|
Sign up to set email alerts
|

Nanoassemblies with light‐responsive size and density from linear flexible polyelectrolytes

Abstract: This study presents electrostatically self‐assembled nanoparticles from linear flexible polyelectrolytes (poly(diallyldimethylammonium chloride or quarternized poly(4‐vinylpyridine)) and an ionic photo‐isomerizable azo dye (Acid Yellow 38) that can change their size upon UV‐light irradiation. Assemblies with narrow size distribution are stable in aqueous solution. For samples with under‐stoichiometric dye load, UV‐light exposure triggers a size decrease, e.g. from a hydrodynamic radius of Rh = 94 nm to Rh = 62… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
3

Year Published

2017
2017
2018
2018

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 87 publications
4
30
3
Order By: Relevance
“…In previous studies, we already investigated the interactions of polyelectrolytes and different azo dyes . These showed that the size of the aggregates is coded by ∆ G .…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…In previous studies, we already investigated the interactions of polyelectrolytes and different azo dyes . These showed that the size of the aggregates is coded by ∆ G .…”
Section: Resultssupporting
confidence: 89%
“…An increasing gain in the free energy Δ G leads to larger hydrodynamic radii R H . Differing results herein are more similar to the observations for trivalent azo dyes, for which also no master curve could be found …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Structure formation can take place via electrostatic interaction with oppositely charged entities, such as ionic porphyrins. During the last years, electrostatic self‐assembly emerged to a powerful tool to create different kinds of supramolecular nanostructures with a variety of shapes . Other noncovalent forces like hydrogen bonding, amphiphilicity, metal coordination, or π–π‐stacking have been exploited for self‐assembly as well.…”
Section: Introductionmentioning
confidence: 99%